Analysis and Evaluation of Bank Credit in Iraq (2010-2018) - Ahmad, Muhsin Ibrahim (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
Bank credit is one of the most important roles of banks in economic activity, whereby banks play an important role in financing the economic and social development process. Considering that, bank credit is the most attractive area of ​​investment for banks due to the high returns achieved from it compared to other investments, which achieves the main goal of banks and is to obtain the largest possible volume of profits. The research is based on the hypothesis that: The banking system was unable to manage the credit process in a manner that leads to the development of the financial system in Iraq, and thus contribute to the development of the Iraqi economy during the period of the research (2010-2018). The research aims to verify the research hypothesis, through analyzing and evaluating the reality of bank credit and its management in Iraq during the period of the research, using a number of criteria and indicators approved in this field.